A review on electrospun nanofibers for photocatalysis: Upcoming technology for energy and environmental remediation applications - Dinesh Pathak; Ankush Sharma; Davinder Pal Sharma; Vinod Kumar (Applied Surface Science Advances, 2023)
Developing an effective artificial photosynthesis system that imitates natural photosynthesis is a major contemporary problem. Electrospun nanofiber (NF) photocatalysts have a lot of promise for solving worldwide environmental and energy problems. Additionally, there are still many challenges to overcome in order to increase photocatalytic efficiency, including solar energy usage and restrictions on carrier lifetime. Different adaptive approaches have been devised and successfully implemented in NF photocatalysts to address these issues. The primary goal of this review paper is to summarize the basic concepts and bottleneck of the photocatalytic process. Following that, various approaches to extend the range of light absorption and photocatalytic applications of NFs are methodically discussed. The ways of prolonging the lifetime of electrons and holes, also known as charge carriers generated by light absorption in electrospun NFs photocatalysts by incorporating heterojunctions and defective formulation, are also discussed in this article. The review concludes with an overview and some thoughts on NF photocatalysts' future directions. We expect this review to add to an understanding of electrospun NFs for photocatalytic applications.